ANALISIS PERAN REGULATOR DAN ASPEK BIAYA DALAM PENCEGAHAN PRAKTIK PREDATORY PRICING DI ECOMMERCE INDONESIA - Biantara, Dheny; Margaretha, Viona; Lesmana, Iwan (Indonesian Journal of Accounting and Governance, 2022)
This study analyzes the role of regulators in Indonesia and the cost aspects that can preventpredatory pricing in an E-Commerce. Cross-border sellers who are successful in offering lower pricesin Indonesian E-Commerce bring concerns and threats to local MSMEs. The government as theregulator decided to prohibit the import of 13 product categories in the E-Commerce marketplace toanticipate unhealthy business practices. This phenomenon is also known as predatory pricing. . Theparameters used in this study are product similarity, selling price and other information that can beused to support research analysis. Grouping product categories and confirming products is a way tounderstand the phenomena that occur in data taken from the Shopee E-Commerce marketplace whichfocuses on competition between domestic sellers where there are 13 products with "overseas" locationfilters no longer found. The analysis of this study shows that all categories experience marketingpractices, and predatory pricing practices can be prevented.